THEMATIC LEARNING WITH A SCIENTIFIC APPROACH IN ELEMENTARY SCHOOL: TEACHERS’ PERCEPTIONS - Sahabuddin, Erma Suryani; Widya Karmila Sari Achmad,; Nur Fadhilah Alam,; Latri, Latri (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: Thematic learning with a scientific approach is being implemented in elementary schools. This approach highlights integrated and comprehensive learning on specific topics or themes, using the scientific method as the foundation for learning. This study aims to analyze teachers' perceptions of thematic learning with a scientific approach in elementary schools. The research employs a quantitative descriptive method, with teachers from upper-grade classes, specifically grades 4, 5, and 6, in 10 clusters of Mariorawa District Gugus 26 Primary Schools in Soppeng Regency as the subjects. The data collection was conducted by distributing questionnaires based on the topic. The results indicate that teachers' knowledge, thinking abilities, and emotional responses fall into the 'very good' category. However, the aspect of teachers' experience falls into the 'good' category. Therefore, this research is expected to contribute to the development of more effective policies and learning programs and to improve student learning outcomes. Abstrak: Pembelajaran tematik dengan pendekatan saintifik merupakan salah satu pendekatan yang dapat digunakan dalam pembelajaran di sekolah dasar. Pendekatan ini menitik beratkan pada pembelajaran yang terpadu dan komprehensif pada suatu topik atau tema tertentu, dengan menggunakan metode saintifik sebagai landasan pembelajarannya. Penelitian ini bertujuan untuk menganalisis persepsi guru terhadap pembelajaran tematik dengan pendekatan saintifik di sekolah dasar. Jenis penelitian ini adalah penelitian deskriptif kuantitatif dengan subjek penelitian yaitu guru pada kelas tingkat tinggi yaitu kelas 4, 5, dan 6 pada 10 kelompok Sekolah Dasar Gugus 26 Kecamatan Mariorawa Kabupaten Soppeng. Pengumpulan data dilakukan dengan menyebarkan kuesioner sesuai topik. Hasilnya menunjukkan bahwa aspek pengetahuan, kemampuan berpikir, dan perasaan guru berkategori sangat baik. Namun, aspek pengalaman guru berkategori baik. Dengan demikian, penelitian ini diharapkan dapat berkontribusi dalam membuat kebijakan dan program pembelajaran yang lebih efektif dalam meningkatkan hasil belajar siswa.